Types of (what) in the Diwan of Abu Naas An applied grammatical study (Journal of the College of Basic Education, 2023)
Praise be to God who sent down the Qur’an in a clear Arabic language, and prayers and peace be upon the elite of creation.And the beloved of truth is Muhammad, his family, his companions, and those who follow them in righteousness until the Day of Judgment.And yet, the collections of poets did not get enough of the grammatical lesson, as most of them were devoted toStudies on the Holy Qur’an, and for this reason I chose Abu Nawas’ Diwan, one of the poets of the Abbasid era.who had a major role in poetry.The research is in three studies:The first topic: dealt with (what) negation and elaborated on its implementation and neglect, thenI chose poetic models to be applied poetic evidence on (what) negation.In the second topic: I talked about (what) the superfluous and the infinitive, and detailed the saying inconditions, and divided (what) the infinitive into two parts:What is the source code:What is the circumstantial source:Then I chose poetic models as poetic evidence applied to (what) the infinitive and (what) the auxiliary.The third topic: I devoted it to the nominal (what) types and divided it into three sections:connecting, exclamatory, and interrogative forms, then I chose poetic models as applied evidence on the types of(what) noun.It relied on a variety of sources, the basis of which is the Diwan of Abu Nawas, as it is the home of research and thenSeparate grammatical books, namely: Al-Kitab by Sibawayh (180 e), and Al-Muqtadab by al-Mubarrad (285 e).Al-Mufassal by Ibn Ya’ish (643 AH) and the paving of buildings by Al-Malqi and Al-Jana Al-Dani by Al-Mardi (741 AH)and others.In conclusion, I hope that I have succeeded in completing this research, and God grant me success.